PENGARUH PERSONAL SELLING DAN SALES PROMOTION TERHADAP PURCHASE INTENTION PADA PRODUK DIABETASOL (STUDI KASUS KONSUMEN PT. KALBE NUTRITIONAL RS.SYAFIRA PEKANBARU) - Erik Estrada; Wilda Sari; Heffi Christya Rahayu (Bajang Institute, 2025)
The research aims to: 1) Analyze the influence of personal selling on purchase intention for Diabetasol products at PT. Kalbe Nutritional Pekanbaru, 2) To analyze the influence of sales promotion on purchase intention for Diabetasol products at PT. Kalbe Nutritional Pekanbaru. Based on the type of data and analysis, this research uses a quantitative type of research, which explains the causal relationship between variables through testing hypotheses that have been previously formulated. The location of this research was carried out at PT. Kalbe Nutritional Pekanbaru in July 2024. The data collection technique in this research used a non-probability sampling technique with purposive sampling. Data collection for this research used a questionnaire with 100 respondents. Data collection methods use primary and secondary data. The research results show that the variables Personal Selling and sales promotion have a significant influence simultaneously on purchase intention.